(Ointment Formulation from N-Hexane Extract of Majapahit Leaves (Crescentia cujete l.) and its Antibacterial Activity Evaluation against Pseudomonas aeruginosa) - Fery I Armadany; Andi E.P. Putri; Erlina D. Sasmin; Mallarangeng Andi N.T.A. Mallarangeng (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
ABSTRACT Background:  Majapahit leaves (Crescentia cujete L.) are known to contain biochemical compounds namely tannins, terpenoids, alkaloids, and saponins which are effective as antimicrobials. Objective(s): This study aimed to formulate ointment from n-hexane extract of majapahit leaves and to known its antimicrobial activity against P. aeruginosa. Methods: ointment ingredients are vaselin, cera alba, liquid paraffin, and menthol and 2% of Majapahit leaves n-hexane extract. Ointment stability test included organoleptic, homogeneity, viscosity, pH, and irritation tests. Evaluation of stability of ointment was obtained by using cycling test method. The irritation test was carried out by open patch test on 6 panellists. Diffusion method is used to obtain antimicrobial activity. Results: The antimicrobial   activity    (diameter   inhibition   zone)   of    the    ointment    against Pseudomonas aeruginosa bacteria was 11 mm and the positive control was 13 mm. The formula showed no change on texture, colour, aroma, viscosity, homogeneity, but there was slight increase in viscosity and pH. The ointment showed non-irritating for panellists thus the ointment formulation is safe for topical use. Conclusion: 2% n-hexane extract of Majapahit leaves can be formulated into ointment with good stability with strong antibacterial activity and non-irritating. Keywords:  antibacterial  activity,  majapahit  leaves,  N-hexane  extract,  ointment,  Pseudomonas aeruginosa